Conversion of T Follicular Helper Cells to T Follicular Regulatory Cells by Interleukin‐2 Through Transcriptional Regulation in Systemic Lupus Erythematosus. Issue 1 (10th November 2020) - Hao, He; Nakayamada, Shingo; Yamagata, Kaoru; Ohkubo, Naoaki; Iwata, Shigeru; Inoue, Yoshino; Zhang, Mingzeng; Zhang, Tong; Kanda Satoh, Yurie; Shan, Yu; Otsuka, Takashi; Tanaka, Yoshiya
Abstract : Objective: This study was undertaken to identify characteristics of follicular regulatory T (Tfr) cells and elucidate the mechanisms by which follicular helper T (Tfh) cells convert to Tfr cells. We probed the phenotype of T helper cells in patients with systemic lupus erythematosus (SLE) and underlying transcriptional regulation using cytokine‐induced STAT family factors. Methods: Peripheral blood mononuclear cells from 41 patients with SLE and 26 healthy donors were used to sort out the memory Tfh cell subset, and Tfh cells were cultured under various conditions. The phenotype of T helper cells and underlying mechanisms of transcriptional regulation were probed using flow cytometry and quantitative polymerase chain reaction analyses. These analyses evaluated the expression of characteristic markers and phosphorylation of STATs. Chromatin immunoprecipitation was used to evaluate histone modifications. Results: In patients with SLE, the proportion of CD4+CXCR5+FoxP3–PD‐1 high Tfh cells was increased ( P < 0.01), whereas the proportion of CD4+CXCR5+CD45RA–FoxP3 high activated Tfr cells was decreased ( P < 0.05). Serum interleukin‐2 (IL‐2) levels were also reduced in patients with SLE. IL‐2 induced conversion of memory Tfh cells to functional Tfr cells, which was characterized by CXCR5+Bcl‐6+FoxP3 high pSTAT3+pSTAT5+ cells. The loci of FOXP3 and BCL6 at STAT binding sites were marked by bivalent histone modifications. Following IL‐2 stimulation, STAT3 and STAT5 selectively bound to FOXP3 and BCL6 gene loci accompanied by suppression of H3K27me3. Finally, IL‐2 stimulation suppressed the generation of CD38+CD27 high plasmablasts in Tfh and B cell coculture assays ex vivo. Conclusion: Impaired function of Tfr cells might be attributed to defective IL‐2 production. Exogenous IL‐2 restores the function of Tfr cells through the conversion of Tfh cells to Tfr cells in patients with SLE. Thus, restoring balance between Tfh and Tfr cells may provide new therapeutic approaches in SLE.